A geographic approach to carbon accounting of Wisconsin. Issue 2 (14th March 2016) - Huang, Wei; Deng, Chengbin
Abstract : Carbon accounting is becoming increasingly important in the way it provides a comprehensive perspective of carbon balance from both carbon emission and carbon assimilation. Numerous previous researches have focused on carbon emission inventory, but few have put their effort in estimating the overall carbon balance as well as analyzing its spatial distribution. In this study, the fossil fuel consumption from all end-use sectors was used to estimate the carbon emission, and the carbon assimilation of vegetation was derived from Moderate Resolution Imaging Spectroradiometer net primary production. Then, the carbon emission was integrated with carbon assimilation to estimate carbon balance. The results were presented in five different maps with a scale of 1:1, 480, 000 and suggested that, in 2009, Wisconsin was able to assimilate its all end-use carbon emissions through the vegetation. In addition, carbon surplus and carbon deficit of Wisconsin demonstrated their respective spatial patterns. The approach can be generalized and applied to other regions to estimate carbon balance.